Effect of Lactobacillus reuteri on vitamin B12 content and microbiota composition of furu fermentation. (February 2019) - Bao, Xuan; Xiang, Shasha; Chen, Jie; Shi, Yugang; Chen, Yuewen; Wang, Huanhuan; Zhu, Xuan
Abstract: In order to solve problems of fluctuant vitamin B12 contents in furu, the effect of L. reuteri inoculation on vitamin B12 content of furu in a large scale experiment was studied in addition to evaluating the microbiomes of furus. Results showed that vitamin B12 content in furu inoculated with L. reuteri was gradually increased up to 141.7 ng/g (wet weight), which is higher than the control group (36.0 ng/g). After principal component analysis, samples for bacterial composition in L. r. group were gathered together, but those for the composition of fungi were dispersed. L. reuteri inoculation obviously increased the relative abundance of Firmicutes and Actinobacteria, but reduced the relative amount of Proteobacteria. The group of L. r. and control exhibited a similar pattern of fungi changes. Based on spearman analysis, Lactobacillus, Enterococcus, Streptococcus, and Corynebacteria were reported to be positively related with vitamin B12 contents and supported each other, vice versa Rhodotorula and Penicillium . Regarding the results of PICRUSt, vitamin B12 related genes pathways were enhanced after L. reuteri was applied. In this study, the novel start culture of L. reuteri was successfully introduced to a traditional soybean fermented food to improve the content of vitamin B12 in furu. Highlights: L. reuteri can enhance vitamin B12 content of furu in a large scale experiment. L. reuteri increased the relative abundance of Firmicutes and Actinobacteria. L. reuteri decreased the relative amount of Proteobacteria. L. reuteri did not affect fungal composition in furu. Lactobacillus supported the growth of Streptococcus and Corynebacteria in furu.